2003
DOI: 10.1021/la026992z
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation Behavior of C60-End-Capped Poly(ethylene oxide)s

Abstract: Single- and double-C60-end-capped poly(ethylene oxide)s (PEOs) were prepared by reacting azido-terminated PEO with C60. The aggregation behavior of these polymers in THF and water was studied by gel permeation chromatography, static and dynamic laser light scattering, and transmission electron microscopy. The solvent polarity, the amount of C60, and the length of PEO segments significantly affect the conformation and the size distribution of aggregates or clusters. The aggregation number of single-C60-end-capp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
112
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(115 citation statements)
references
References 41 publications
2
112
0
Order By: Relevance
“…For example, micelle-like core-shell aggregates with shells containing highly-stretched polymer chains were reported for PMMA-b-C 60 and PnBMA-b-C 60 systems in THF [11]. Song et al reported large spherical aggregates for single-and two-arm fullerene-containing poly(ethylene oxide)s in THF and aqueous solution [12], [13]. Although the above polymers were synthesized by cycloaddition reaction of azide-terminated polymers with fullerene, the atom transfer radical polymerization (ATRP) technique has recently been used to synthesize well-defined fullerene-containing polymers.…”
Section: Introductionmentioning
confidence: 99%
“…For example, micelle-like core-shell aggregates with shells containing highly-stretched polymer chains were reported for PMMA-b-C 60 and PnBMA-b-C 60 systems in THF [11]. Song et al reported large spherical aggregates for single-and two-arm fullerene-containing poly(ethylene oxide)s in THF and aqueous solution [12], [13]. Although the above polymers were synthesized by cycloaddition reaction of azide-terminated polymers with fullerene, the atom transfer radical polymerization (ATRP) technique has recently been used to synthesize well-defined fullerene-containing polymers.…”
Section: Introductionmentioning
confidence: 99%
“…It is similar to the fullerene aggregates observed for the fullerene capped PEO. 29 The fullerene aggregates were formed by the aggregation of fullerenes grafted to the PCL chain. This result verified our previous prediction that the fullerene introduced onto the PCL grafts can aggregate into the fullerene particles.…”
Section: Resultsmentioning
confidence: 99%
“…The resulted double-fullerene end-capped PEO (FPEOF) showed excellent mechanical properties. [25][26][27][28][29] The aggregation of the fullerene moieties in the double capped polymer leads to the formation of network-like structures so that a combination of a double-fullerene capped polymer and a linear polymer is expected to give rise to a pseudo-semi-interpenetrating polymer network (p-SIPN). Poly(methyl methacrylate) (PMMA) blended with FPEOF shows a good reinforced toughness.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of p-SIPN will result in enhancement of the mechanical properties of PLLA. [37,43,44] The PLLA/FPEOF composite samples with PLLA in its amorphous state showed good tensile properties. An astounding fracture strain was observed and there was an optimum value for the content of FPEOF to achieve the highest fracture strain.…”
Section: Mechanism Of Enforcing Effect Of Fpeofmentioning
confidence: 98%